Penerapan Teori Joe Goldblatt pada Pameran Sense of Basokie Abdullah di Museum Nusa Tenggara Barat - Muhammad Arfa; Sasih Gunalan; Haryono Haryono; Haryono Bayu Aji Pamungkas (JURNAL RUPA, 2022)
The Basokie Abdullah Sense of Exhibition was held at the West Nusa Tenggara Museum in collaboration with several communities. This study aims to identify and formulate a new model of exhibition. This research uses descriptive qualitative method adopted from Joe Goldblatt’s theoretical approach through 5 phases. The research results reveal that two exhibitions were formulated namely Special Event. This exhibition has positive response from audiences based on the interview. This study contributes to the new model in exhibition that carried out local values.